Implementation of Professional Ethical Values in Higher Education Curriculum - Syafa’tul Habib; Redhi; Shalman Alvarishi (Penerbit Hellow Pustaka, 2025)
Professional ethics are the main foundation in shaping the character and integrity of prospective professionals in various fields. This article comprehensively discusses the implementation of professional ethics values in the higher education curriculum as part of an effort to form graduates who are not only academically competent, but also morally and socially responsible. Using a descriptive-qualitative approach, the discussion includes the integration of ethical values in curriculum design, teaching practices, campus culture, and the role of lecturers and institutions. The findings show that an integrated approach, involving cross-subject learning, behavioral role models, and strengthening institutional policies, is an effective strategy in internalizing ethical values. Despite facing various challenges such as dualism between technical and ethical competence, unpreparedness of human resources, and limited regulations, opportunities for strengthening ethics remain open through national policy support, utilization of technology, and multi-stakeholder collaboration. This article recommends a transformation of higher education that places ethics as a key element in curriculum development and education governance, in order to produce graduates with integrity and social responsibility.